2023
DOI: 10.3390/polym15030712
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Technologies of Polymer Composites—A Review

Abstract: Polymer composites have been widely used in the aviation, aerospace, automotive, military, medical, agricultural and industrial fields due to their excellent mechanical properties, heat resistance, flame retardant, impact resistance and corrosion resistance. In general, their manufacturing process is one of the key factors affecting the life cycle of polymer composites. This article provides an overview of typical manufacturing technologies, including surface coating, additive manufacturing and magnetic pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 166 publications
0
8
0
Order By: Relevance
“…Various mechanical sensor types have been used for biomedical engineering applications including piezoelectric, capacitive, and piezoresistive sensors. Due to their versatile strain-sensing abilities, easy readout, and low energy requirements, piezoresistive materials have been widely investigated for robotics, biomedicine, and other applications (e.g., for biometrics and prosthetics), and enable wearable electronic devices, electronic skin, and flexible sensors, and implantable interfaces (34,35). Despite their potential for sensing technologies, using piezoresistive composites for biomedical sensors remains underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanical sensor types have been used for biomedical engineering applications including piezoelectric, capacitive, and piezoresistive sensors. Due to their versatile strain-sensing abilities, easy readout, and low energy requirements, piezoresistive materials have been widely investigated for robotics, biomedicine, and other applications (e.g., for biometrics and prosthetics), and enable wearable electronic devices, electronic skin, and flexible sensors, and implantable interfaces (34,35). Despite their potential for sensing technologies, using piezoresistive composites for biomedical sensors remains underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The fabrication of 3D objects equipped with locomotion ability is called 4D printing, which first appeared in 2013. With the advances of this novel concept, the application scope of 4D printing has been extended to self‐assembly, [ 197 ] self‐adaptation, [ 198 ] and self‐healing. [ 199 ] Currently, there is a wide range of applicable 4D‐printing methods, including direct inkjet curing, [ 200 ] fused deposition modeling, [ 201 ] stereolithography, [ 202 ] laser‐assisted bioprinting, [ 203 ] and selective laser sintering.…”
Section: Soft Materials and Fabrication Methodsmentioning
confidence: 99%
“…Duan et al [ 22 ] prepared a Triton X-100-modified fluorinated graphene and ZIF-8 composite epoxy coating, and the tests showed that the CoF of the coating was 0.15 under dry sliding wear at a load of 5 N and a sliding speed of 10 mm/s. The polymer coating is not only self-lubricating but also corrosion resistant [ 23 , 24 , 25 ]. Ren et al [ 26 ] prepared an h-BN@PDA epoxy coating and found that the corrosion potential of the composite coating in a 3.5 wt% NaCl solution was 0.1 V. Gu et al [ 27 ] studied the effect of modified graphene oxide (BGO) on the corrosion resistance of epoxy coatings and found that the resistance of the epoxy coating with 0.1 wt% BGO was 1.03 GΩ·cm 2 in a 3.5 wt% NaCl solution.…”
Section: Introductionmentioning
confidence: 99%